2014
DOI: 10.1007/s00441-014-1907-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanical loading on osteogenesis of human dental pulp stromal cells in a novel in vitro model

Abstract: Tooth loss often results the alveolar bone resorption due to lack of mechanical stimulation. Thus, the mechanism of mechanical loading on stem cells osteogenesis is crucial for alveolar bone regeneration. This project aims to investigate the effect of mechanical loading on human dental pulp stromal cells (hDPSCs) osteogenesis in a novel in vitro model. Briefly, 1×10 7 hDPSCs were seeded into 1 mL 3% agarose gel in a 48-well-plate. Then a loading tube was placed in the middle of the gel to mimicking the tooth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Other groups have successfully implanted hydroxyapatite/agarose hydrogels as bone graft material, proving osteoconductive properties of composites ( 26 , 28 ). Furthermore, the osteogenic differentiation of dental stromal cells under mechanical stimulation in agarose gels has been recently described ( 29 ). The ASNIS-III s screw was set in the centre of the 3D osteoblast-agarose scaffold to expose the bone cells to the EMF + EF.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have successfully implanted hydroxyapatite/agarose hydrogels as bone graft material, proving osteoconductive properties of composites ( 26 , 28 ). Furthermore, the osteogenic differentiation of dental stromal cells under mechanical stimulation in agarose gels has been recently described ( 29 ). The ASNIS-III s screw was set in the centre of the 3D osteoblast-agarose scaffold to expose the bone cells to the EMF + EF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using a bioreactor that mimicked biting force, Ji et al (2014) successfully developed a novel method to enhance the osteogenic differentiation of DPSCs. They showed that the application of mechanical forces that mimicked the dynamics of those exerted in vivo on DPSCs could be used to promote bone formation and limit bone resorption ( Ji et al, 2014 ).…”
Section: Mechanical Stimuli That Induce Osteogenic Differentiation Ofmentioning
confidence: 99%
“…Several investigations have also shown that mechanical stimuli including dynamic hydrostatic pressure, cyclic tensile strain, mechanical compression and cyclic uniaxial compressive strain can promote the odontogenic differentiation of DPSCs ( Yu et al, 2009 ; Lee et al, 2010 ; Miyashita et al, 2017 ; Yang et al, 2017 ). While other studies have demonstrated that cyclic mechanical tension, pulsating fluid flow, surface topographies, equiaxial static tensile strain and mechanical loading can promote the osteogenic differentiation of DPSCs ( Han et al, 2008 , 2010 ; Kraft et al, 2010 , 2011 ; Ji et al, 2014 ; Kolind et al, 2014 ; Tabatabaei et al, 2014 ). Interestingly, mechanical forces such as uniaxial stretch can increase the proliferation of DPSCs while inhibiting the odontogenic and osteogenic differentiation of DPSCs, indicating that mechanical stimuli are therefore critical and contextually important in modifying DPSC fate ( Cai et al, 2011 ; Hata et al, 2012 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This extends previous studies where mineralization and mature bone formation was found to be increased by mimicking vascularization in vitro in cocultures of endothelial cells and human MSC. [57][58][59][60] It is also important to consider that ADSCs have previously been shown to exhibit a proangiogenic effect via release of angiogenic factors such as vascular endothelial growth factor (VEGF), differentiate into endothelial cells in vitro and improve postnatal neovascularization in vivo. [61][62][63] The data shown here further support the proangiogenic potential of these cells which then augments their osteogenic maturation capabilities.…”
Section: D Culture and Vascularization Promote Hadsc Osteogenesis mentioning
confidence: 99%